Basic & clinical pharmacology - Katzung, Bertram G.; Masters, Susan B.; Trevor, Anthony J. (New York : McGraw-Hill Medical ; London : McGraw-Hill [distributor], 2009)
Looks at the essential conepts in the science of pharmacology and its application to clinical practice
Basic principles -- Autonomic drugs -- Cardiovascular-renal drugs -- Drugs with important actions on smooth muscle -- Drugs that act in the central nervous system -- Drugs used to treat diseases of the blood, inflammation, & gout -- Endocrine drugs -- Chemotherapeutic drugs -- Toxicology -- Special topics
"A Lange medical book."
Previous ed.: 2007
Includes bibliographical references and index
13
Keywords: Clinical pharmacology; Pharmacology